Design and Fabrication of Ball Punch Deformation Test of Metallic Sheet Material - Citra Asti Rosalia; Satrio Wicaksono; Tatacipta Dirgantara; Arif Basuki; Ichsan Setya Putra (Mesin, 2018)
Predicting the behavior of sheet metal in forming process is very important to avoid material failure. The strain limit of sheet metals before tearing occurs is attainable in Forming Limit Diagram (FLD), which can be obtained experimentally or theoretically. Experimentally, FLD of a sheet metal can be achieved by performing ball punch deformation test. Unfortunately, commercially available ball punch deformation test apparatus is still very expensive. In this paper, the design, fabrication and testing process of more affordable ball punch deformation test apparatus is be presented. The ball punch apparatus has indenter's diameter of 22.4 mm, which capable to tear 0.2-2.0 mm thick specimen blanks with maximum capacity of 200 kN. The test results are then compared with other commercially available ball punch deformation test apparatus results in the literature, and show very good agreement.